Carbene-catalyzed activation of formyl-phenylacetic esters for access to chiral dihydroisoquinolinones - Wu, Shuquan (2022)
A carbene-catalyzed reaction to synthesize chiral dihydroisoquinolinones via an o-quinodimethane (o-QDM) intermediate is disclosed. o-QDM reacts with cyclic sulfonic imines via annulation to afford highly enantioenriched dihydroisoquinolinone products. ESI-HRMS studies suggest a stepwise Mannich addition and acylation reaction pathway, and the pathways of the catalytic and uncatalyzed background reactions are evaluated via DFT calculations.